PROBLEMATIKA PEMBELAJARAN AL-QIRA`AH DAN SOLUSI PEMECAHANNYA: Studi Deskriptif Kualitatif di MA Miftahurrahman Tasikmalaya - Mahmudin, Wildan (THORIQOTUNA: Jurnal Pendidikan Islam, 2018)
The purpose of learning Arabic in general is so that studentscan master Arabic well and correctly. To achieve this goal, of course,can not be separated from several factors, namely teachers, students,material, methods and environment. From these factors must bemutually supportive of one another. As in learning Al-Qira`ah in Arabicat MA Miftahurrahman Tasikmalaya to achieve the goals to beachieved there are problems that must be faced by students andteachers, namely linguistic and non-linguistic problems. To get the factsabout the existing reality about the problems of learning Al-qira`ah inMA Miftahurrahman Tasikmalaya, the author uses several methods,namely methods of interviews, observation, questionnaires, tests anddocumentation. And to analyze the data that has been collected, theauthors use a descriptive analysis method. And so that this research canbe well directed, the writer uses learning theory and problematic theoryin learning Al-Qira`ah. Because in a study can be said perfectly, if inlooking for existing data must be in accordance with the theory andnone other than this kind of research that is qualitative research can besaid with proof of a theory. The results of this study regarding theproblems of Al-Qira`ah learning problems in MA MiftahurrahmanTasikmalaya and their solutions, namely: 1) The implementation of Al-Qira`ah teaching activities in MA Miftahurrahman Tasikmalaya as wellas activities in madrassas which include teaching objectives,curriculum , teachers, students and methods; 2) In learning al-qira`ahmaharah in MA Miftahurrahman Tasikmalaya, teachers and students experience problems that include linguistic and non-linguistic problemssuch as teacher, student, method, and environment; 3) the solution ofthe problem solving is that the teacher must have the ability to masterthe Al-Qira`ah learning method, students must be disciplined infollowing the learning, the method used is the eclectic method, and theright environment for learning Al-Qira`ah Arabic is language orboarding environment